TINJAUAN HUKUM ISLAM TENTANG JUAL BELI TUAK NIRA - Misnawati zakfah (IAIN BONE, 2022)
AbstractThis article discusses the legal issues of buying and selling palm wine from the point of view of Islamic law, which aims to find out the law of buying and selling palm wine. This article uses library research methods in obtaining data, as well as with qualitative descriptive analysis. The results of the discussion show that palm wine is actually similar to khamr in terms of Islamic law, so its legal status can be determined through the qiyas method. So the law of drinking palm wine is haram. Based on the shari'i argument presented, it is concluded that the prohibition of alcoholic liquor, not only for those who drink it, but for those who sell it, even all those involved will get a sin.Keywords: Khamr; Islamic Law; Palm Wine.